Use of educational platforms in the process of learning English language skills. - Barragán Lucas, Sonia (Revista Universidad de Guayaquil, 2023)
The use of platforms in the teaching-learning process at a higher level is currently a resource widely used by educational institutions, in the case of the Naval High School in the Naval Sciences Career is no exception since in the English subject it is quite common to use didactic resources of this type to comply with the development of English language learning skills. The type of research applied was quantitative, cross-sectional, descriptive in relation to the use of educational platforms in the learning process of English language skills, in the Naval Science High School, for which 80 students from different years were surveyed to know their level of knowledge in relation to the use of educational platforms and how they influence the teaching-learning process, where it is evident that different platforms and resources of this type are used to improve the learning of this language.
Keywords: English language teaching; platforms; resources and institutions